Live online lecture versus classroom lecture: perception of undergraduate medical and nursing students and faculty - Bashyal, Ritu; Devbhandari, Ranjan; Pradhan, Prasil; Byanju, Jayandra; Aryal, Sushant; Maharjan, Babu Raja (Journal of Patan Academy of Health Sciences, 2022)
Introduction: During COVID-19 pandemic, live online lectures were offered for the first time to the undergraduate students. Due to its novelty, it was important to identify the effectiveness. Thus, the aim of this study was to compare the perception of students and faculty regarding the attributes of lectures delivered via live online versus classroom platform.Method: In this descriptive study, after approval from the ethical committee, link to the validated questionnaire was sent via email to all participants. Quantitative data were expressed as numbers and percentage while thematic analysis was done for qualitative data.Result: In this study 22 faculty members and 176 students participated. Twenty-one (95%) faculty and 159 (90.3%) students agreed that it was a good initiative to start live online lectures during the pandemic, and 18 (81.8%) faculty and 160 (91%) students were satisfied or partially satisfied with online mode. Limitations identified were technical issues and lack of physical interaction. Both faculty members 18 (81.8%) and students 116 (65.9%) agreed or strongly agreed that online lectures were less interactive, and suggested ways to improve online lectures by making sessions more interactive, proper lecture scheduling and using different online media.Conclusion: Participants identified various strengths of live online mode which is encouraging to use during adverse situations or even continue as a standard platform but it is not without limitations. Thus, for successful implementation, proper planning and designing of lectures are required.